Investigator Initiated Clinical Trials (IICTs): A Systematic Search in Registries to Compare the Czech Republic and Portugal in Terms of Funding Policies and Scientific Outcomes - Madeira, C; Hořavová, L; Dos Santos, F; Batuca, J R; Nebeska, K; Součková, Lenka; Kubiak, C; Demotes, J; Demlová, R; Monteiro, E C (Therapeutic innovation & regulatory science, 2021)
OBJECTIVES: Clinical trials provide one of the highest levels of evidence to support medical practice. Investigator initiated clinical trials (IICTs) answer relevant questions in clinical practice that may not be addressed by industry. For the first time, two European Countries are compared in terms of IICTs, respective funders and publications, envisaging to inspire others to use similar indicators to assess clinical research outcomes. METHODS: A retrospective systematic search of registered IICTs from 2004 to 2017, using four clinical trials registries was carried out in two European countries with similar population, GDP, HDI and medical schools but with different governmental models to fund clinical research. Each IICT was screened for sponsors, funders, type of intervention and associated publications, once completed. RESULTS: IICTs involving the Czech Republic and Portugal were n = 439 (42% with hospitals as sponsors) and n = 328 (47% with universities as sponsors), respectively. The Czech Republic and Portuguese funding agencies supported respectively 61 and 27 IICTs. Among these, trials with medicinal products represent 52% in Czech Republic and 4% in Portugal. In the first, a higher percentage of IICTs' publications in high impact factor journals with national investigators as authors was observed, when compared to Portugal (75% vs 15%). CONCLUSION: The better performance in clinical research by Czech Republic might be related to the existence of specific and periodic funding for clinical research, although further data are still needed to confirm this relationship. In upcoming years, the indicators used herein might be useful to tracking clinical research outcomes in these and other European countries.
Keywords: Policy; Česká republika; Registries; registrace; retrospektivní studie; lidé; postup; Portugalsko; Retrospective Studies; Czech Republic; Portugal; Humans